Poster: Using the analytical network process for controller placement in software defined networks - Ali, Jehad; Lee, Seungwoon; Roh, Byeong Hee (MobiSys 2019 - Proceedings of the 17th Annual International Conference on Mobile Systems, Applications, and Services, 2019)
The Software Defined Networking (SDN) paradigm has shifted the network intelligence from the network devices to the centralized controller. The controllers are placed in a distributed manner in a network for reliability and load balancing. However, the placement of controllers considering the whole network is not an efficient approach because applying the objective function to the overall network is a challenging task. Therefore, the division of the network into clusters makes the assignment of the switches to the controller more efficient. The placement of the controller in a cluster not only reduces the latency between the switches and the controller but other objectives such as reliability, load balancing, robustness and energy saving can also be applied to the clusters. Therefore, in this poster, a multi-criteria-decision-making (MCDM) scheme known as the Analytical Network Process (ANP) is proposed for controller place selection using clustering.
Keywords: Analytical network process; Analytical network processes (ANP); Centralized controllers; Controller placements; Multi objective; Multi-criteria decision making; Network intelligence; Software defined networking (SDN); Analytical network process; Controller placement problem; Multi-objective; SDN